Ultrasound-Guided Measurement of Piriformis Muscle Thickness to Diagnose Piriformis Syndrome - Siahaan, Yusak Mangara Tua; Tiffani, Pamela; Tanasia, Amanda (Frontiers in Neurology, 2021)
Background: Piriformis syndrome (PS) is a neuromuscular condition caused by the entrapment of the sciatic nerve at the level of the piriformis muscle (PM). Diagnosing PS remains challenging despite recent invasive and non-invasive diagnostic methods. Response to invasive nerve block is still one of the most reliable diagnostic modalities because there is no gold standard test for PS. As early diagnosis may prevent delayed diagnosis that results in chronic somatic dysfunction and muscle weakness, a screening test with high sensitivity could guide clinicians in performing the next appropriate step in diagnosing PS. Aim: The purpose of this study is to determine the sensitivity, specificity, and best cut-off point of ultrasound-guided PM thickness in PS. Method: This case-control study was conducted in a general hospital in Tangerang during a 3-month period. We recruited 58 patients clinically diagnosed with PS and 58 healthy patients (without a history of hip and buttock pain) during their visits to the outpatient clinic. All patients underwent ultrasound assessment to measure bilateral PM thickness. Sex, age, body mass index, history of micro-/macro-trauma, and prolonged sitting duration were recorded. Statistical analyses were performed using the Statistical Package for the Social Sciences version 25. Result: The PS and control groups predominantly comprised female subjects, with mean ages of 51.79 ± 14.10 and 50.09 ± 13.26 years on PS and healthy subjects, respectively. The mean ultrasound-guided PM thickness was higher in PS subjects compared to healthy subjects with mean thicknesses of 1.16 ± 0.13 and 0.85 ± 0.11 cm, respectively (p < 0.05). The area under the receiver operating characteristic curve of the PM was 0.970 (95% confidence interval 0.943–0.998, p < 0.05). The best cut-off point defined by Youden's J index was 0.9950 cm for all PS subjects. Conclusion: We propose 0.9950 cm as the cut-off point for diagnosing PS by ultrasound, which has the sensitivity and specificity of 94.8 and 87.9%, respectively.